Rzemiosło sztuki prawniczej, czyli o niełatwej sztuce pisania trudnych uzasadnień - Mróz, Katarzyna (PRAWO i WIĘŹ, 2026)
This paper presents the heuristic value of analysing the judicial model of dispute resolution in the context of practical discourse, in the light of the main contemporary theories of legal discourse. Judicial activism, manifested in a willingness to depart from established practices and models in case law in order to interpret legal norms, has become a leading factor in an in-depth reflection on the postulate of effective communication and a universal understanding of the law. The manner and form in which judgments are reasoned form part of the contemporary debate on the relationship between justice in the postmodern era and the culture of legal language. This paper contributes to research on the use of judicial analysis of the law in contemporary legal discourse.